MP024: Ultrasound-guided femoral nerve block versus fascia iliaca block for hip fractures in the emergency department: a randomized pilot study. (2nd June 2016) - Chenkin, J.; Lee, J.S.; Bhandari, T.; Simard, R.
Abstract : Introduction: Regional anesthesia has been shown to be an effective pain control strategy for patients presenting with hip fractures in the emergency department. There are two common methods for performing this block: the femoral nerve block (FNB) and the fascia iliaca compartment block (FICB). The objective of this pilot study is to determine whether one of these two ultrasound-guided block techniques provides superior analgesia to emergency department patients with hip fractures.Methods: Emergency physicians at a single institution were randomized to the FNB or FICB training groups. Participants completed a 2-hour practical workshop covering the technique, followed by a questionnaire to assess their comfort with the block. They were asked to perform their assigned nerve block on any patient in the ED presenting with a hip or femur fracture. Physician comfort level and patient pain scores using a visual analog scale (VAS) were recorded before and after the nerve block were recorded. Comparisons were performed using Student's t-test and Fisher's exact test.Results: A total of 20 physicians were enrolled in the study, 10 in the FNB group and 10 in the FICB group. There were no significant baseline differences between the groups with respect to ultrasound or nerve block experience. Following the training, 100% of participants in both the FNB group and FICB group felt comfortable performing the block. Nerve blocks were performed in 30/51 (58.8%) of eligible patients in the FNB group and 6/11 (54.5%) in the FICB group (p=1.0). On the 10-point VAS, pain scores decreased by a mean of 4.9 (SD 3.5) in the FNB group and 8.3 (SD 2.4) in the FICB group (p=0.056). In practice, physicians felt comfortable performing the FNB in 52.8% of cases, and the FICB in 85.7% of cases (p=0.21). Mean time to completion of the blocks was similar between the two groups (19 vs 18 mins, p=0.83).Conclusion: In this pilot study, we found a non-significant trend towards improved analgesia and higher physician comfort with the ultrasound-guided FICB compared with the FNB in patients with hip fractures. We found no differences in time to performing the blocks. These results require confirmation with a larger sample size.